BAGAIMANAKAH PENAFSIRAN UJIAN KOMPREHENSIF MENURUT CIVITAS AKADEMIK UNIVERSITAS TRUNOJOYO? - Robiatul Auliyah; Nurul Herawati; Aprillia Dwi Utami (Universitas Trunojoyo Madura, 2011)
Comprehensive exam is compulsory for every student of accounting in order to be graduated from the school. From the academic data of 2007 to 2009, the number of student that failed from the comprehensive exam was increasing. This fact becomes the main reason for taking this study, hence, the main purpose of this study is to interpret comprehensive exam based on the understanding of the lecturers, alumni, and students of Trunojoyo University. Informants on this study consist of lecturers, alumni, and students. There are 8 informants that is used in this study, in which 3 of them are lecturers, 2 of them are students, and the other 3 are alumni. Furthermore, this study incorporates qualitative methodology with interpretive paradigm and also use phenomenology approach. The result of this study shows that all of the academic members have the same understanding on comprehensive exam. According to their understanding, comprehensive exam is a final exam which is based on the subjects of accounting department from the very first semester to the last semester. In addition, factors that support the success of student on the comprehensive exam are, first, the lecturer subjectivity in marking the student, even though not all lecturers are subjective while marking the student. Second is the psychological condition of the student during the comprehensive exam. Third is the level of understanding of the student itself on the accounting subjects that has been taken by the student. The last is related to the time when the comprehensive exam took place in which has the same time with thesis examination.